Polioencephalomalacia in buffaloes (Bubalusbubalis) in a feedlot - Victor Alexandre Nascimento Silva; Marcio Alan Oliveira Moura; Antonio Elivelton Coutinho de Souza; Arieli Sousa de Oliveira; Valíria Duarte Cerqueira; Gabriela Riet Correa Rivero; Pedro Soares Bezerra Júnior (Ciência Rural, 2023)
ABSTRACT: Polioencephalomalacia (PEM) is a nervous disease that affects ruminants, has a worldwide distribution and causes significant economic losses. PEM is abundantly described and studied in cattle and small ruminants, but there is little information about the disease in buffaloes, especially in Brazil. The objective of this work is to describe the clinical and pathological aspects of an outbreak of PEM in buffaloes in a feedlot in the state of Pará, Brazil. The outbreak occurred in a flock of 76 Murrah buffaloes, with an average age of five months, in a feedlot. Twenty-eight of these buffaloes became ill, and thirteen showed neurological signs and died. Two buffaloes underwent necropsy. The brain and fragments of various abdominal and thoracic cavity organs were fixed in 10% formalin and sent for histopathological examination. In the frontal, parietal, and occipital telencephalic lobes, the convolutions were flattened and yellowish, and when cut, there was a clear line of demarcation between the superficial and deep layers. Histologically, the intermediate layers of the cerebral cortex showed mild to moderate vacuolization of the neuropil, moderate enlargement of the perivascular, perineuronal, and periastrocyte spaces, moderate swelling and edema of astrocytes, and a large number of necrotic neurons. The work demonstrates that, despite being poorly documented in Brazil, PEM should be considered in the differential diagnosis of neurological syndromes in buffaloes.